INVESTMENT ALTERNATIVES IN THE MEXICAN REAL ESTATE SECTOR: CROWDFUNDING AND STOCK INVESTMENT. - Burgos Ojeda, Sergio Armando (Posgrados de la División de Ciencias Económica Administrativas, 2022)
Real Estate investment is mainly characterized by the acquisition of real estate, forcing the investor to own or acquire a considerable amount of capital to obtain it. Due to the difficulties that the averagae investor has to participate in the real estate sector, the crowdfunding model enters this sector, offering an opportunity to participate in various real estate projects around the mexican republic. The objective of this work is to evaluate the investment alternatives in the real estate sector. For this purpose, the Markowitiz modelo of portfolio optimization is applied, developing a code sequience in Rstudio and a financial model in Microsoft Excel. The main risk-adjusted return indicators that are adapt to both portfolios are used to reinforce portfolio management decisión making. It is concluded, from the results obtained, that the crowdfungding projects are an investement alternative that is eventually more financially attractive than the stock market investment portfolio.